2014
DOI: 10.1186/1472-6882-14-415
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng extract and ginsenoside Rb1 attenuate carbon tetrachloride-induced liver fibrosis in rats

Abstract: BackgroundGinsenosides, the major bioactive compounds in ginseng root, have been found to have antioxidant, immunomodulatory and anti-inflammatory activities. This study investigated the effects of ginsenosides on carbon tetrachloride (CCl4)-induced hepatitis and liver fibrosis in rats.MethodsMale Sprague–Dawley rats were randomly divided into four groups: control, CCl4, CCl4 + 0.5 g/kg Panax ginseng extract and CCl4 + 0.05 g/kg ginsenoside Rb1 groups. The treated groups were orally given Panax ginseng extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 43 publications
1
36
1
2
Order By: Relevance
“…It should be noted that CCl 4 was given at a relatively high dosage, allowing an induction of liver cirrhosis in a short period. This might account for the severe liver dysfunction and cirrhosis in the CCl 4 -treated rats in the present study, relative to previous reports [38][39][40].…”
Section: Bcl-2-modified Bmscs Attenuated Serological and Histologicalcontrasting
confidence: 53%
See 1 more Smart Citation
“…It should be noted that CCl 4 was given at a relatively high dosage, allowing an induction of liver cirrhosis in a short period. This might account for the severe liver dysfunction and cirrhosis in the CCl 4 -treated rats in the present study, relative to previous reports [38][39][40].…”
Section: Bcl-2-modified Bmscs Attenuated Serological and Histologicalcontrasting
confidence: 53%
“…* p < 0.05, ** p < 0.01, compared to week 1 in the same group. + p < 0.05, ++ p < 0.01, compared to the cirrhosis+saline group at the same time point Experimental cirrhosis was induced in rats by intraperitoneal injection of CCl 4 using established methods [38][39][40]. It should be noted that CCl 4 was given at a relatively high dosage, allowing an induction of liver cirrhosis in a short period.…”
Section: Bcl-2-modified Bmscs Attenuated Serological and Histologicalmentioning
confidence: 99%
“…In addition, IL-10 induces the downregulation of T helper 1 cytokine mRNA expression, and inhibits IL-1 and IL-6 production (37,38). In the present study, CCl 4 -induced downregulation of IL-10 is consistent with the findings of a previous study, which reported that CCl 4 reduced hepatic IL-10 expression, as compared with in the control group (39). In the present study, POM upregulated IL-10 expression, thus suggesting that POM exerts an anti-inflammatory effect, which protects the liver from CCl 4 -induced inflammation.…”
Section: A B Csupporting
confidence: 93%
“…Xie XS, et al have demonstrated that ginsenoside Rb1 alleviates renal interstitial fibrosis in unilateral ureteral obstruction (UUO) rat model [ 37 ]. Moreover, ginsenoside Rb1 has been demonstrated to be effective in attenuating liver fibrosis in vitro and in vivo [ 11 , 24 ]. Our results showed that ginsenoside Rb1, especially H-ginsenoside Rb1, and losartan reduced the expression levels of Ang II, ACE, AT1 receptor, periostin and collagen I in a rat model of HF.…”
Section: Discussionmentioning
confidence: 99%